(untitled) (Research, Society and Development, 2021)
Objective: to analyze the prevalence of polypharmacy and the pharmacotherapeutic profile of elderly people enrolled in a family health unit. Methods: Cross-sectional, quantitative, descriptive and analytical pharmacoepidemiological study, carried out with individuals aged 60 years or more in the city of Lafaiete Coutinho – BA. The association between variables was tested using Poisson Regression, with robust calculation of prevalence ratios (PR) and 95% confidence interval (95%CI) and significance p<0.05. Results: 70 elderly people participated; the prevalence of polypharmacy was 24.3% and was significantly associated with the use of health services at least once a year (PR=1.44; CI=0.29-3.67; p<0.001) or for more than twice a year (PR=3.43; CI=1.61-7.43; p<0.01); to the elderly who do not know the indication of their medications (PR=7.40; CI=1.37-39.89; p=0.02), to those who reported complaints about medications (PR=4.09; CI=0. .78-21.42; p=0.04) and those who need some resource to remember to take their medications (PR=4.17; CI=0.97-17.94; p=0.05). The factor helping to take the medication was shown to be a protective factor (PR=0.19; CI=0.03-1.00; p=0.02). Conclusion: The prevalence of polypharmacy was considerable and suggests the need for greater awareness on the part of health professionals, regarding the monitoring of potential risks and associated benefits, in order to ensure the safe use of drugs in polypharmacy regimens in these elderly people.